2016
DOI: 10.1515/bglass-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vivo angiogenetic effects of copper doped bioactive glass scaffolds in the AV loop model

Abstract: Abstracteffects of 3D scaffolds made from 45S5 bioactive glass (BG) doped with 1 wt. % copper ions in the arteriovenous loop model of the rat.Materials and Methods: An arteriovenous loop was built in the groin of 10 rats and inserted in 1% copper doped 45S5 BG scaffolds and fibrin. The scaffold and the AV loop were inserted in Teflon isolation chambers and explanted 3 weeks after implantation. Afterwards the scaffolds were analyzed by Micro-CT and histology regarding vascularization. Results were compared to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…However, we may speculate whether the S53P4 BaG itself promotes angiogenesis, and the addition of Cu 2+ that was released from the scaffold of PCL:S53P4–Cu1 = 4:1 does not suffice to produce observable differences in tubular network formation. A similar finding was also reported in an in vivo evaluation of the angiogenetic effect of the Cu-doped 45S5 scaffolds in the AV loop model: a tendency toward an increased vascularization in the Cu-doped BaG group compared to the plain BaG group was observed in μ-CT and histological evaluations, but no statistical difference in vascularization could be measured between both groups . Altogether, the PCL:S53P4 = 4:1 and PCL:S53P4–Cu1 = 4:1 scaffolds supported the vascularization and tubular formation in the coculture setup; however, the angiogenic effect of Cu 2+ was not notable in contrast to the PCL/BaG composite.…”
Section: Discussionsupporting
confidence: 86%
“…However, we may speculate whether the S53P4 BaG itself promotes angiogenesis, and the addition of Cu 2+ that was released from the scaffold of PCL:S53P4–Cu1 = 4:1 does not suffice to produce observable differences in tubular network formation. A similar finding was also reported in an in vivo evaluation of the angiogenetic effect of the Cu-doped 45S5 scaffolds in the AV loop model: a tendency toward an increased vascularization in the Cu-doped BaG group compared to the plain BaG group was observed in μ-CT and histological evaluations, but no statistical difference in vascularization could be measured between both groups . Altogether, the PCL:S53P4 = 4:1 and PCL:S53P4–Cu1 = 4:1 scaffolds supported the vascularization and tubular formation in the coculture setup; however, the angiogenic effect of Cu 2+ was not notable in contrast to the PCL/BaG composite.…”
Section: Discussionsupporting
confidence: 86%
“…Altogether, neither of these therapeutic ions had any biological influence on the immune response or the vascularization pattern. This result is surprising as both ions have been described to influence both molecular cascades but are in line with another in vivo study including an analysis of silicate-based copper-doping that also showed no influence and, more importantly, the materials in fact hindered the regeneration process (62,64).…”
Section: Discussionsupporting
confidence: 51%
“…The release of Ca 2+ ions is also suspected to play an important role in the late stages of healing, and the presence of calcium in the immediate vicinity of an open wound seems to help the body to regulate wound healing processes more effectively, particularly in open wounds. Doping with small amounts of selected ions, e.g., Cu 2+ [ 89 ], can further potentiate the angiogenetic effect of BGs. Copper is known to regulate a number of factors involved in angiogenesis, such as vascular endothelial growth factor (VEGF), fibronectin, angiogenin, and fibroblast growth factor (FGF) 1 and 2, which play key roles in the initiation (vasodilation and vascular permeabilization), maturation (endothelial cell proliferation, migration and morphogenesis), and regulation of blood vessel formation (ECM remodeling) [ 90 ].…”
Section: Grand Challenges For the Future—where Are We Going?mentioning
confidence: 99%